Tre amici tra la Sardegna e Ferrara Le lettere di Mario Pinna a Giuseppe Dessí e Claudio Varese - Dessì, Giuseppe (Moderna/Comparata, 2013)
A private and distant Sardinia animates the texts of this double correspondence, between archaic landscapes and personal and literary mythologies, in which Ferrara, the town of the authors' youthful years, is occasionally mentioned, with its richness of life, magazines (Bottai's «Primato», «Corriere Padano» with Bassani...), evening meetings in taverns or rented rooms, walks along the Rampari river, and the use of playful nicknames which would continue even after youth ended. A world made of concrete things, animated and enlivened by strong intellectual curiosities and passions, emerges from the letters reconstructing the life and history of Giuseppe Dessí, Mario Pinna and Claudio Varese, which have been carefully transcribed and annotated by Costanza Chimirri. The correspondence opens with the years spent in Ferrara - after Pisa, a crucial moment for their education - and allows the author to reconstruct atmospheres and environments, readings and work, offering a significant cross-section of twentieth-century Italy from within. The letters are never disconnected from one another, but rather united by the continuous call to the triple friendship in the name of Giuseppe Dessí, who is always present in the others' speeches even when he is not actually mentioned. The correspondence also allowed to bring to light unpublished texts by the most secluded member of the group (Mario Pinna, an avid reader of the classics, Spanish specialist, author of poems in the dialect of Logudoro and of short stories set in Sardinia), to strengthen the role that has always been played by the eldest, Claudio Varese, the maître-camarade; and to confirm once again how much Dessí's creative universe, deeply marked by the biographical element, has continued to develop and feed under the wise and affectionate gaze of fraternal friends, in an exchange which can give life to an actual collective imagination.